2015
DOI: 10.1007/s12185-015-1825-x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of adolescent patients with acute myeloid leukemia treated with pediatric protocols

Abstract: As past studies of adolescent and young adults (AYA) with acute myeloid leukemia (AML) reported conflicting results, we conducted a retrospective analysis using data from three Japanese pediatric AML studies. Among the 782 patients with de novo AML, 44 were classified as AYA (age ≥15 years at diagnosis), 164 as infants (0-1 year), 413 as younger children (2-11 years), and 161 as older children (12-14 years). While the 5-year event-free survival rate of AYA was not different among the groups, the five-year surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 32 publications
4
15
0
Order By: Relevance
“…Similar findings were reported for TRM rates in patients aged 10–21 years in the St. Jude Children's Research Hospital AML protocols (1991–2008) . Survival rates for Japanese patients aged 15–17 years were lower than those for younger patients, mainly due to a higher TRM rate after relapse …”
Section: Predictors Of Outcomesupporting
confidence: 78%
See 1 more Smart Citation
“…Similar findings were reported for TRM rates in patients aged 10–21 years in the St. Jude Children's Research Hospital AML protocols (1991–2008) . Survival rates for Japanese patients aged 15–17 years were lower than those for younger patients, mainly due to a higher TRM rate after relapse …”
Section: Predictors Of Outcomesupporting
confidence: 78%
“…45 Survival rates for Japanese patients aged 15-17 years were lower than those for younger patients, mainly due to a higher TRM rate after relapse. 46…”
Section: Predictors Of Outcomementioning
confidence: 99%
“…In multivariate analysis, they demonstrated that age $15 years is associated with a nearly threefold increase in the risk for TRM (hazard ratio [HR] 5 2.789; 95% confidence interval [CI], 1.437-5.412; P 5 .002). 6 Studies from the COG have also highlighted the high risk for TRM among AYA patients. In an analysis encompassing 4 COG trials (Children's Cancer Study Group [CCG] 2891, CCG 2941, CCG 2961, and AAML 03P1) and 1840 patients, Canner et al compared outcomes in patients 16 to 20 years of age to those in younger patients.…”
Section: Predisposition To Treatment-related Mortality With Pediatricmentioning
confidence: 99%
“…Evidence is increasingly showing the superiority of the pediatric approach for the management of AYA patients with ALL. However, the data on AML are very limited [3] and only a few retrospective studies of AYA patients with AML have compared pediatric and adult approaches [4][5][6][7][8][9]. Although allogeneic hematopoietic stem cell transplantation (HSCT) is an important curative option for both children and adults with AML, only a few reports have examined the procedure in AYA patients with AML [10,11].…”
Section: Introductionmentioning
confidence: 99%